Prevalence and associated factors of soil transmitted helminthes infestation among preschool children of Vadamaradchi Educational Zone - Karunaithas, R.; Murugananthan, A.; Kannathasan, S. (Faculty of Science, University of Jaffna, 2011)
This cross sectional study was designed to find out the prevalence of soil transmitted helminth infestation and associated factors among preschool children of Vadamaraadchi Educational Zone in Jaffna district. One preschool was randomly selected from each division (3) of the educational zone, and all the children (n=103) of selected schools were included in the study. Faecal samples were collected and examined by direct wet smear, salt flotation and formal ether concentration techniques. Demographic, socio-economic and health related behavior data were obtained from the parents using interviewer administered questionnaire. Prevalence of soil transmitted helminthes was zero in this study. Majority of the fathers were fishermen (55%), whereas most of the mothers were housewives (86%). Sixty five percentage (65%) of fathers and 68% of mothers studied up to G.C.E O/L. Eighty nine (86%) parents were aware of worm infestation. Ninety nine (96%) stated that they cleaned their children after defecation. Among them, the majority always (88%) and a few (8%) sometimes washed their hands with soap and water after cleaning. Almost an equal proportion of children used water sealed toilets (48%) and open ground (47%) for defecation. Fifty two (50%) children always and 43 (42%) children sometimes used foot ware when they went out. Most of the children (96%) received antihelminthic drugs. Seventy two children (70%) received the drug within the last 3months. The study indicates, the reduction in the prevalence of soil transmitted helminthes could be mainly due to anti-helminthic prophylaxis and practice of hand washing by the parents. A case control study has to be carried out to confirm the above conclusion. The majority (70%) received more frequent anti helminthic prophylaxis. As there are reports of anti helminthic resistance, further study is needed to find out the appropriate intervals at which anti-helminthic prophylaxis to be given.
Keywords: Soil Transmitted Helminthes; preschool children; antihelminthic prophylaxis